2020
DOI: 10.1016/j.jaci.2020.07.026
|View full text |Cite
|
Sign up to set email alerts
|

Asthma among hospitalized patients with COVID-19 and related outcomes

Abstract: Background Several underlying conditions have been associated with severe acute respiratory syndrome coronavirus 2 illness, but it remains unclear whether underlying asthma is associated with worse coronavirus disease 2019 (COVID-19) outcomes. Objective Given the high prevalence of asthma in the New York City area, our objective was to determine whether underlying asthma was associated with poor outcomes among hospitalized patients with severe COVID-19 compared with pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
75
1
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(93 citation statements)
references
References 48 publications
14
75
1
3
Order By: Relevance
“…Although both these views seem logical, they were questioned by a group of other authors, among whom Jackson et al [32] demonstrated significantly reduced ACE2 gene expression in the airway epithelium of asthmatic patients, which interferes with SARS-CoV-2 entry to host cells, and according to these authors, decreases the probability of severe COVID-19 in these patients. This view has been confirmed by Lovinsky-Desir et al in New York [33] who found that asthma diagnosis was not associated with worse outcomes in patients with severe COVID-19, and by Chhiba et al [34] in Chicago who stated that in COVID-19 patients, asthma was not associated with an increased risk of hospitalization, in spite of the fact that asthma prevalence in this group (14.4%) was significantly greater compared with the general US and metropolitan Chicago population ranging from 8 -9.5%. A view on the under-representation of asthma among COVID-19 patients was shared by a group of other authors [7,35,36] who mentioned three reasons for this: reduced expression of ACE2 and TMPRSS2 enzymes in host cells, protective antiviral effects of cytokines and accumulation of eosinophils occurring in type 2 immune response occurring in asthma, and possible beneficial effects of drugs used for the treatment of asthma.…”
Section: Annals Of Agricultural and Environmental Medicinesupporting
confidence: 59%
See 1 more Smart Citation
“…Although both these views seem logical, they were questioned by a group of other authors, among whom Jackson et al [32] demonstrated significantly reduced ACE2 gene expression in the airway epithelium of asthmatic patients, which interferes with SARS-CoV-2 entry to host cells, and according to these authors, decreases the probability of severe COVID-19 in these patients. This view has been confirmed by Lovinsky-Desir et al in New York [33] who found that asthma diagnosis was not associated with worse outcomes in patients with severe COVID-19, and by Chhiba et al [34] in Chicago who stated that in COVID-19 patients, asthma was not associated with an increased risk of hospitalization, in spite of the fact that asthma prevalence in this group (14.4%) was significantly greater compared with the general US and metropolitan Chicago population ranging from 8 -9.5%. A view on the under-representation of asthma among COVID-19 patients was shared by a group of other authors [7,35,36] who mentioned three reasons for this: reduced expression of ACE2 and TMPRSS2 enzymes in host cells, protective antiviral effects of cytokines and accumulation of eosinophils occurring in type 2 immune response occurring in asthma, and possible beneficial effects of drugs used for the treatment of asthma.…”
Section: Annals Of Agricultural and Environmental Medicinesupporting
confidence: 59%
“…In contrast to other allergic and immunotoxic diseases that may be due to bioaerosol exposure, the significance of asthma in relation to COVID-19 has been studied and discussed by many authors [29][30][31][32][33][34][35][36][37][38][39][40]. Nevertheless, the data interpretation and conclusion formulation are difficult because of the variable prevalence of asthma in the general population, which is usually much greater in the USA and…”
Section: Respiratory Diseases Caused By Exposure To Occupational Bioamentioning
confidence: 99%
“…16 However, subsequent reports from around the world have suggested that asthma may not be risk factor for severe COVID-19, including hospitalization and death. 6,8,[17][18][19] However, these reports have largely been limited by several factors including the inclusion of other chronic pulmonary conditions (e.g. COPD) in populations studied, conditioning on patients who were hospitalized with COVID-19, 18 and/or not accounting for secular changes in COVID-19 testing criteria.…”
Section: Discussionmentioning
confidence: 99%
“…6,8,[17][18][19] However, these reports have largely been limited by several factors including the inclusion of other chronic pulmonary conditions (e.g. COPD) in populations studied, conditioning on patients who were hospitalized with COVID-19, 18 and/or not accounting for secular changes in COVID-19 testing criteria. 20 Our study improves upon these prior studies by rigorously defining asthma, excluding those with non-asthma chronic pulmonary conditions (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Severe asthma was associated with increased risk of COVID-19-related death in one study reviewing a health analytics platform with records of 40% of England's patients, 149 but asthma was not necessarily associated with increased mortality in other studies. 147,[150][151][152] Interestingly, in at least two studies where asthma was associated with worse clinical outcomes, non-allergic asthma accounted for the increased risk for worse outcomes (severe COVID-19, ICU admission, intubation, death). 145,153 J o u r n a l P r e -p r o o f…”
Section: Clinical Manifestations Among Patients With Allergy and Atopymentioning
confidence: 99%